A preparation process of high-quality Mg-Li and Al-Li alloys with large melting volume under normal pressure

By preparing composite oxides containing metal lithium and Li-Mg binary alloys under normal pressure, combined with paraffin purification and distillation purification processes, the problems of flammability, segregation and high equipment costs in the preparation of magnesium lithium and aluminum lithium alloys in the prior art are solved, and the preparation of high-quality and low-cost large-scale melting alloys are achieved.

CN119351806BActive Publication Date: 2025-03-18SHANXI JIN SOUTHEAST SHENHUA NEW MATERIAL CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411899451.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-23
Publication Date
2025-03-18
Estimated Expiration
2044-12-23

AI Technical Summary

Technical Problem

The prior art has problems such as metal lithium flammability, reaction generation impurities, thermal cracking, high equipment costs, and serious segregation when preparing magnesium lithium and aluminum lithium alloys, which are difficult to meet the needs of large smelting furnaces in the fields of aerospace and other fields.

Method used

Using the normal pressure process, a composite oxide containing metal lithium is first prepared, and then a high-temperature vacuum heat reduction reaction is used to form a Li-Mg binary alloy. After paraffin purification, distillation purification and ingot casting process, high-quality Mg-Li and Al-Li alloys are finally prepared with magnesium ingots or aluminum ingots.

Benefits of technology

It effectively improves the yield of lithium and the quality of alloys, reduces equipment investment, solves segregation and impurities problems, meets the demand for large melting alloys and large castings, and avoids the pollution caused by chlorine gas produced by traditional lithium electrolysis.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119351806B_ABST
    Figure CN119351806B_ABST
Patent Text Reader

Abstract

The present application belongs to the field of light metal alloy smelting. In order to meet the market demand for high-quality magnesium-lithium and aluminum-lithium alloy large ingots, the present application provides a preparation process of high-quality Mg-Li and Al-Li alloys with large smelting amount under normal pressure. First, a lithium source and Ca, Mg, and Al oxides are used to prepare Li-Mg binary alloy elements through reduction reaction, and the Li-Mg binary alloy elements are smelted with magnesium ingots or aluminum ingots under normal pressure to obtain corresponding Mg-Li or Al-Li alloys. The present application method can prepare high-quality Mg-Li and Al-Li alloy large castings at normal pressure, while improving the yield of lithium, without using electrolytic lithium metal as raw material for preparing magnesium-lithium or aluminum-lithium alloys, thereby avoiding the pollution of chlorine produced by traditional lithium electrolysis.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the field of light metal alloy smelting, and specifically relates to a preparation process of high-quality Mg-Li and Al-Li alloys with large smelting volume under normal pressure. Background Art

[0002] Magnesium-lithium and aluminum-lithium alloys are the lightest among metal structural materials. The density of magnesium-lithium alloy is 1.3-1.6g / cm 3 , the density of aluminum-lithium alloy is 2.45-2.80g / cm 3 , with high specific strength, specific stiffness, specific damping performance, good low-temperature plasticity and impact resistance, good corrosion resistance and fatigue resistance, excellent heat dissipation performance, etc. It is used in many industries and high-tech civilian fields such as aerospace, aviation, navigation, ordnance, nuclear reactors, tank armor-piercing shells, torpedoes, automobiles, robots, and electronic products, attracting many scientists around the world to study magnesium-lithium and aluminum-lithium alloys, which has led to the rapid development of magnesium-lithium and aluminum-lithium alloys.

[0003] At present, the method for producing magnesium-lithium and aluminum-lithium alloys at home and abroad is to use the alloying method in a vacuum furnace, that is, high-quality aluminum ingots that meet GB / T 1196-2008 or high-quality magnesium ingots that meet GB / T3499-2023 are melted into liquid at 750-780℃ in a crucible in a vacuum furnace, and metallic lithium is added to the aluminum liquid or magnesium liquid by the bell jar method to obtain aluminum-lithium or magnesium-lithium alloys. However, the main problems of the alloys prepared by this process are:

[0004] 1. Directly adding metallic lithium to magnesium liquid or aluminum liquid, because metallic lithium is active and flammable, and easily reacts with oxygen, nitrogen, water, etc. in the air, resulting in a reduced lithium yield, and the compounds generated by the reaction increase the impurities in the alloy liquid. The gas impurities generated by the reaction cause thermal cracking of the alloy, and it is impossible to obtain high-quality magnesium-lithium and aluminum-lithium alloy large castings, which cannot meet the needs of large melting furnaces in specific fields such as aerospace;

[0005] 2. The requirements for reaction equipment are high. The alloy melting furnace used is a vacuum melting furnace, which is not completely domestically produced and has a large fixed asset investment;

[0006] 3. During alloying, the alloy cannot be fully stirred. At the same time, the melting point, density and other properties of metallic lithium, magnesium and aluminum are too different, resulting in serious segregation, which makes the absolute strength, stiffness and modulus of the alloy low;

[0007] 4. The electrolysis of lithium first requires a complex process to obtain pure lithium chloride. When lithium chloride is electrolyzed to generate metallic lithium, chlorine gas is released, which has high manufacturing costs, large fixed asset investments, and is difficult to address environmental issues. Summary of the invention

[0008] In order to meet the market demand for high-quality magnesium-lithium and aluminum-lithium alloy large ingots, the present application provides a preparation process for high-quality Mg-Li and Al-Li alloys with large smelting amounts under normal pressure.

[0009] A preparation process of high-quality Mg-Li and Al-Li alloys with large smelting amount under normal pressure, comprising the following steps:

[0010] S1. Preparation of a composite oxide containing metallic lithium: The lithium source and the oxide are fully mixed and pressed into a cylinder, and calcined at a high temperature in a vacuum to obtain a composite oxide containing metallic lithium;

[0011] S2. Preparation of Li-Mg binary alloy: The composite oxide prepared in step S1 is fully mixed with a reducing agent and a flux and then pressed into pellets, the pellets are subjected to a high-temperature vacuum thermal reduction reaction to generate a lithium and magnesium metal mixture gas, the metal mixture gas is cooled in a cooling collector to form a metastable metallic bond Li-Mg binary alloy condensed phase;

[0012] S3. Paraffin purification: The Li-Mg binary alloy condensed phase collected in step S2 is placed in the melted paraffin together with the collector, so that the Li-Mg binary alloy condensed phase is completely melted and floats on the surface of the paraffin, and the high melting point impurities sink to the bottom of the paraffin, the temperature of the paraffin is lowered, and the Li-Mg binary alloy liquid phase floating on the surface of the paraffin solidifies into a solid phase and is removed;

[0013] S4. Distillation, purification and ingot casting: The solidified Li-Mg binary alloy condensed phase removed from step S3 is distilled and purified in a distillation furnace protected by argon gas, and the purified Li-Mg binary alloy is smelted in a smelting furnace and a flux is added, and cast into a Li-Mg binary alloy ingot under argon gas protection, and is packed with aluminum foil and stored in an argon-filled container;

[0014] S5. Alloying of magnesium and aluminum: heating and melting the washed and dried magnesium ingot or aluminum ingot in an electric furnace, placing the Li-Mg binary alloy ingot obtained in step S4 into the molten magnesium liquid or aluminum liquid for smelting, rapidly melting the Li-Mg binary alloy ingot, stirring, cooling, and then casting to obtain the corresponding magnesium-lithium alloy ingot or aluminum-lithium alloy ingot.

[0015] Furthermore, the mass ratio of the lithium source and the oxide in step S1 is (35-45):(65-55); the lithium source is one, two or three of anhydrous lithium carbonate, lithium nitrate and lithium hydroxide, and the oxide is a mixture of calcium oxide and magnesium oxide, or a mixture of aluminum oxide and magnesium oxide; the particle size D50 of the lithium source is 75-90 μm, and the particle size D50 of the oxide is 85-100 μm.

[0016] Furthermore, the calcination under vacuum and high temperature in step S1 refers to calcination at a vacuum degree of 5-20 Pa and 850-950° C. for 6-8 hours. The reaction mechanism of calcining lithium source is the same, and the chemical reaction formula is similar. Taking the reaction when calcining lithium carbonate as an example, the reaction formulas of different oxides and lithium carbonate are as follows:

[0017] Li2CO3+MgO=Li2O·MgO+CO2↑

[0018] Li2CO3+CaO=Li2O·CaO+CO2↑

[0019] Li2CO3+Al2O3=Li2O·Al2O3+CO2↑ .

[0020] Furthermore, in step S2, the mass ratio of the composite oxide, reducing agent and flux is (80-83):(15-17):(2-4), and the particle sizes of the composite oxide, reducing agent and flux are all selected such that D50 is 80-90 μm.

[0021] Furthermore, the reducing agent in step S2 is any one of ferrosilicon, aluminum powder or carbon powder, and the flux is fluorite.

[0022] Furthermore, the high-temperature vacuum thermal reduction reaction of the pellets in step S2 is carried out at a pressure of 5-10 Pa and 1100-1200° C. for 8-10 hours, and the reaction of the composite oxide containing metallic lithium obtained by calcination is as follows:

[0023] 2(Li2O·MgO)+Si=2MgO·SiO2+4Li↑

[0024] 2 (Li2O·GaO) + Si = 2CaO·SiO2 + 4Li↑

[0025] 2(Li2O·Al2O3)+Si=2Al2O3·SiO2+4Li↑

[0026] 2(CaO·MgO)+Si=2CaO·SiO2+2Mg↑.

[0027] Furthermore, the melting temperature of the Li-Mg binary alloy condensed phase in the cooling collector in step S3 is controlled to be 7-10°C higher than the melting point of the Li-Mg binary alloy, and the melting time is 2-2.5 hours. After the Li-Mg binary alloy floats on the surface of the paraffin, the temperature of the paraffin is lowered to 5-7°C lower than the melting point of the Li-Mg binary alloy of the component, and the temperature is kept constant for 1-1.5 hours, and the solid is scooped out with a colander.

[0028] Furthermore, in step S4, the Li-Mg binary alloy is subjected to three-stage distillation purification in a distillation furnace, the distillation kettle in the distillation furnace is made of stainless steel, and the three distillation temperatures are respectively controlled to be 15° C., 30° C., and 45° C. higher than the melting point of the Li-Mg binary alloy.

[0029] Furthermore, when the Li-Mg binary alloy is melted in step S4, and when the magnesium ingot or aluminum ingot is heated and melted in step S5, a flux is added and protected by argon gas, and the flux is a mixture of three compounds: LiCl, MgCl2 and LiF, and the mass ratio of the three compounds is LiCl:MgCl2:LiF=(55-65):(4-21):(24-31).

[0030] Furthermore, the metastable metallic bond Li-Mg binary alloy condensed phase is a compound Mg 2.49 Li and Mg 4.72 Li, in step S5, after the Li-Mg binary alloy reaches the melting point and melts, when it is close to 600°C, the compound Mg 2.49 Li and Mg 4.72 Li is decomposed into atomic Li and atomic Mg, and the atomic Li and atomic Mg are evenly distributed in the corresponding magnesium liquid or aluminum liquid through stirring.

[0031] Furthermore, the smelting process in step S5 is carried out under normal pressure, and the smelting furnace is a domestic electric furnace such as a resistance furnace, induction furnace, etc. that can smelt under normal pressure. Such electric furnaces are low in price, and smelting under normal pressure is convenient for large-capacity smelting.

[0032] In summary, the technical method of the present application includes at least one of the following beneficial technical effects:

[0033] 1. The technical method of the present application is to further produce Mg-Li and Al-Li alloys from the intermediate product Li-Mg alloy element, which breaks through the traditional method of using the metal lithium obtained by electrolysis to form an alloy with magnesium liquid / aluminum liquid, solves the problems of serious segregation of metal lithium in the alloy, poor appearance quality, and substandard mechanical properties, and effectively improves product quality;

[0034] 2. The technical method of the present application is not limited by production equipment. Conventional electric furnaces such as resistance furnaces or induction furnaces can be used, which reduces fixed asset investment. The equipment is completely domestically produced and can produce large alloy castings with large smelting volumes, which can fill the current demand for large alloy castings in the fields of aerospace and aviation;

[0035] 3. The intermediate product Li-Mg alloy element prepared in the technical method of this application contains 85-95% lithium, which has not been reported at home and abroad. The rolled thin plate of this alloy is expected to be directly used as the negative electrode of lithium batteries;

[0036] 4. Directly use the mixed oxides of calcium, magnesium and aluminum to obtain magnesium and lithium mixed metal gas by vacuum thermal reduction, and condense the lithium-magnesium binary alloy, which effectively improves the lithium yield;

[0037] 4. It effectively avoids the problem of chlorine gas produced by traditional lithium electrolysis methods and solves the problem of environmental pollution. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] Figure 1 This is a process flow chart of the technical method of this application;

[0039] Figure 2 This is a schematic diagram of the appearance of the LA141 magnesium-lithium alloy product prepared by the technical method of the present application in an electric furnace with a smelting amount of 400kg under normal pressure;

[0040] Figure 3 This is a schematic diagram of the appearance of a 2195 aluminum-lithium alloy product prepared by an electric furnace with a smelting amount of 400 kg under normal pressure using the technical method of the present application;

[0041] Figure 4 This is a schematic diagram of the appearance of the LA141 magnesium-lithium alloy product prepared by the metal lithium doping method in a vacuum electric furnace with a melting capacity of 400kg;

[0042] Figure 5 This is a schematic diagram of the appearance of the LA141 magnesium-lithium alloy product after combustion, which was prepared by the metal lithium doping method in a vacuum electric furnace with a melting capacity of 400kg;

[0043] Figure 6 This is a schematic diagram of the appearance of the 2195 aluminum-lithium alloy product after combustion, which was prepared by the metallic lithium doping method in a vacuum electric furnace with a melting capacity of 400kg. DETAILED DESCRIPTION

[0044] The specific implementation of the present application is further described below in conjunction with the accompanying drawings.

[0045] like Figure 1 As shown in the process flow chart, the core of the technical method of the present application is to first prepare the intermediate product Li-Mg binary alloy ingot, which can also be called Li-Mg binary alloy element or lithium-magnesium alloy element, and then use the lithium-magnesium alloy element and magnesium ingot / aluminum ingot to smelt to obtain the corresponding Mg-Li alloy ingot / Al-Li alloy ingot.

[0046] Example 1

[0047] This embodiment is used to prepare LA141A magnesium-lithium alloy ingots, and the specific preparation process is as follows:

[0048] S1. Select lithium carbonate and calcium oxide as raw materials, the calcium oxide contains a small amount of magnesium oxide, the raw materials are powders with a D50 of 85 μm, and the mass ratio of lithium carbonate and calcium oxide containing a small amount of magnesium oxide is 43:57. Mix the lithium carbonate and calcium oxide powders and press them into a cylinder with a diameter of Φ20mm×25mm at 45MPa using a ball press, and calcine them in a calcining furnace at a vacuum degree of 15Pa and a temperature of 910°C for 8 hours to obtain a composite oxide calcium lithium acid.

[0049] The calcination reaction is as follows:

[0050] Li2CO3+CaO=Li2O·CaO+CO2↑

[0051] Li2CO3+MgO=Li2O·MgO+CO2↑

[0052] At the same time, because lithium carbonate salts are prepared in various ways and with abundant raw materials, when limestone is involved in the raw materials, the dolomite in the limestone undergoes the following reaction during calcination:

[0053] CaC03·MgC03 = Mg0·Ca0+2C02 ↑

[0054] Therefore, if there is limestone in the raw materials, it will not affect the technical method of the present application, and the trace amount of magnesium oxide generated during the calcination process can be used as the reaction raw material of this step.

[0055] Similarly, if aluminum oxide and magnesium oxide are used as the oxide raw materials, the reaction between aluminum oxide and lithium salt is as follows:

[0056] Li2CO3+Al2O3=Li2O·Al2O3+CO2↑.

[0057] S2. Grind the composite calcium lithium oxide, No. 75 ferrosilicon and fluorite into powder with a D50 of 80 μm, mix the calcium lithium oxide: ferrosilicon: calcium fluoride in the mass proportion of 82:16:2, and press the mixed powder into 35 g / almond-shaped pellets at a pressure of 45 MPa using a pellet press, wherein ferrosilicon is a reducing agent and fluorite is a flux; then react the pellets in a vacuum reactor at a vacuum degree of 10 Pa and a temperature of 1150°C for 9.5 hours, and the gas generated by the reaction enters a cooling collector, and the metal contained in the gas phase is condensed into a condensed phase and collected in the cooling collector, thereby obtaining a Li-Mg binary alloy condensed phase with a metastable metallic bond.

[0058] The reduction reaction process is as follows:

[0059] 2(Li2O·MgO)+Si=2MgO·SiO2+4Li↑

[0060] 2 (Li2O·GaO) + Si = 2CaO·SiO2 + 4Li ↑

[0061] 2(CaO·MgO)+Si=2CaO·SiO2+2Mg↑

[0062] Similarly, when aluminum oxide is used in the raw material, the reaction is:

[0063] 2(Li2O·Al2O3)+Si=2Al2O3·SiO2+4Li↑

[0064] S3. Place the collector with the Li-Mg binary alloy condensate phase into a paraffin melt at 220°C. After keeping the temperature constant for 2 hours, cool the paraffin melt to 203°C and keep it warm for 1 hour. The Li-Mg binary alloy liquid phase solidifies into a solid phase. Use a colander to scoop out the solidified Li-Mg binary alloy condensate phase, and the high-melting-point impurities sink to the bottom of the paraffin.

[0065] S4. The Li-Mg binary alloy solid is purified in a stainless steel distillation kettle with three-stage temperature control in series at 235°C, 250°C and 265°C respectively, and the paraffin carried by the Li-Mg binary alloy solid is returned to the paraffin melting furnace, 86% of K and Na are removed by gasification or become another product with high K and Na, and the impurity content of 87% of the Li-Mg binary alloy meets the GB / T4369-2015 standard, and is melted at 280°C in an electric furnace under the protection of a flux with a mass ratio of LiCl:MgCl2:LiF=63:6:31 and argon gas, and the Li-Mg binary alloy liquid is cast into a metal ingot in an argon-filled glove box, and vacuum-packed with aluminum foil to obtain a purified Li-Mg binary alloy ingot. The lithium content of the Li-Mg binary alloy ingot is 95%, and the content of Li+Mg is 99.5%. The obtained Li-Mg binary alloy ingot is used as an alloying element for preparing Mg-Li alloy (magnesium-lithium alloy) and Al-Li alloy (aluminum-lithium alloy) in the future, and is hereinafter referred to as Li-Mg binary alloy element or lithium-magnesium alloy element. Among them, the high melting point impurities are mainly high melting point oxides and fluorides, specifically CaO, MgO, Li2O, 2CaOSiO2, 2CaOLi2O, FeO, Fe2O3, CaF2, a very small amount of Li2O, ferrosilicon, etc.

[0066] S5. Put 200kg of the washed and dried magnesium ingot into a crucible in a normal pressure electric furnace and heat it to 750℃. After 45 minutes, the magnesium ingot is completely melted. 32.7kg of Li-Mg binary alloy elements obtained in step S4 are used to prepare LA141A magnesium-lithium alloy. The aluminum foil-wrapped Li-Mg binary alloy elements are directly placed 300mm below the magnesium liquid. After 5 minutes of melting, mechanical stirring is performed for 25 minutes, cooled to 710℃ and cast into an ingot in a cylindrical mold to obtain a magnesium-lithium alloy ingot. The prepared magnesium-lithium alloy ingot is sampled and analyzed. The yield of metallic lithium reaches 94.35%, and the lithium content at each point in the magnesium-lithium alloy ingot is 14±0.1%. There is no segregation phenomenon. The surface of the ingot is smooth and crack-free. The element composition is tested to meet the high-quality product standard of GB / T3499-2023.

[0067] Example 2

[0068] This embodiment is used to prepare 2195 aluminum-lithium alloy ingots, and the process of preparing lithium-magnesium alloy elements (steps S1-S4) is the same as that of Example 1.

[0069] S5. Put 200kg of washed and dried aluminum ingots into a crucible in a normal pressure induction furnace and heat to 750℃. After 45 minutes, the aluminum is completely melted. Take out 2.49kg of lithium-magnesium alloy elements to prepare 2195 aluminum-lithium alloy. Put the lithium-magnesium alloy elements containing 95% lithium wrapped in aluminum foil 300mm below the aluminum liquid. After 5 minutes of melting, stir mechanically for 25 minutes, cool to 710℃ and use semi-continuous casting to form an ingot to obtain an aluminum-lithium alloy ingot. The sampling and analysis results of the prepared aluminum-lithium alloy ingot show that the yield of metallic lithium is 94.82%, the content of metallic lithium at multiple different locations in the aluminum-lithium alloy is 1.12±0.01%, there is no segregation of metallic lithium in the alloy, the surface of the ingot is smooth, and the elemental composition meets the high-quality product standard of GB / T 1196-2008.

[0070] One of the key points of the technical method of the present application is to first prepare high-quality lithium-magnesium alloy elements (i.e., the intermediate product obtained in step S4), and the main technical indicators of the prepared lithium-magnesium alloy elements are lithium yield, Li+Mg content, and Li content. Based on Example 1, the lithium yield, (Li+Mg) content, and Li content of the lithium-magnesium alloy elements are analyzed for different technical parameters of step S1 (calcination section), step S2 (vacuum thermal reduction section), and step S3 (paraffin purification section). The results are shown in Table 1. Except for the variable parameters in the table, the rest of the preparation process and the detection and analysis process are exactly the same as those in Example 1.

[0071] Table 1:

[0072]

[0073] As can be seen from Table 1, the high-quality lithium-magnesium alloy element first obtained by the technical method of the present application has a Li content of not less than 85%, a Li+Mg content of not less than 99.5%, a Li yield of more than 90%, and even a Li yield of more than 96% in Examples 4 and 5. The above examples prove that the process route of the technical method of the present application is smooth, and the process parameters and selected equipment can meet the requirements for preparing lithium-magnesium alloy elements. The lithium-magnesium alloy manufactured by this method is 2 / 3 of the manufacturing cost of traditional metal lithium, which can greatly reduce the manufacturing cost of magnesium-lithium alloy and aluminum-lithium alloy; the alloying preparation process does not require the use of expensive vacuum melting furnaces, and the fixed asset investment is reduced by 1 / 3 compared with the same lithium output, and there is no chlorine pollution.

[0074] Among them, the high-temperature vacuum thermal reduction reaction of step S2 is a solid-solid reaction, that is, the reactants are all solid and produce gas. In order for the solid-solid reaction to proceed, the contact area must be expanded, so the material must be ground finely, but if it is too fine, the surface energy of the material will increase and it will naturally polymerize. Therefore, a certain particle size should be selected to increase the reaction speed and yield. Similarly, pressurization is also to allow molecules to approach better to react. Therefore, the particle size of the lithium source in the calcination section step S1 is generally D50 of 75-90μm, the particle size of the oxides of calcium, magnesium, and aluminum is generally D50 of 85-100μm, and the particle size of the raw material in the vacuum thermal reduction section step S2 is D50 of 80-90μm.

[0075] In order to further verify the effectiveness and advantages of the technical method of the present application, the technical method of the present application is compared with the method of preparing magnesium-lithium alloys and aluminum-lithium alloys with different smelting amounts by the doping method. The comparative analysis results of preparing LA141 magnesium-lithium alloy are shown in Table 2, and the comparative analysis results of preparing 2195 aluminum-lithium alloy are shown in Table 3.

[0076] Table 2:

[0077]

[0078] Table 3:

[0079]

[0080] The specific preparation process of Comparative Example 1 in Table 1 and Comparative Example 4 and 5 in Table 2 is as follows:

[0081] Comparative Example 1

[0082] The magnesium-lithium alloy is prepared by the doping method: 200 kg of the washed and dried magnesium ingot is placed in a crucible in a vacuum induction furnace, vacuumed and filled with argon to maintain a slight positive pressure, heated to 750 ° C, and the magnesium is completely melted after 45 minutes. 37.90 kg of metallic lithium obtained by electrolysis and vacuum-packed with aluminum foil is taken out to prepare LA141A magnesium-lithium alloy ingots. The metallic lithium wrapped in aluminum foil is placed 300 mm below the magnesium liquid by the bell jar method. After the melting is completed in 5 minutes, argon is passed and stirred for 25 minutes, cooled to 710 ° C and cast into a cylindrical casting. The prepared magnesium-lithium alloy ingot is sampled and analyzed. The yield of metallic lithium is 74.1%, the highest point of lithium content is 16.63%, the lowest point is 12.36%, and the metallic lithium is severely segregated in the alloy. The electrolysis method in this comparative example is a known technology and will not be described in detail in this application.

[0083] Comparative Example 4

[0084] Preparation of aluminum-lithium alloy by doping method: 200 kg of washed and dried aluminum ingots are placed in a crucible in a vacuum induction furnace, evacuated and filled with argon to maintain a slight positive pressure, and heated to 750°C. After 45 minutes, the aluminum is completely melted, and 2.89 kg of metallic lithium obtained by electrolysis and vacuum-packed in aluminum foil is taken out. The target alloy is 2195 aluminum-lithium alloy ingot. The metallic lithium wrapped in aluminum foil is placed 300 mm below the aluminum liquid by the bell jar method. After melting in 5 minutes, argon is passed and stirred for 25 minutes, cooled to 710°C and semi-continuously cast into ingots. The prepared aluminum-lithium alloy ingots are sampled and analyzed. The yield of metallic lithium is 73.82%, the highest lithium content is 1.96%, and the lowest lithium content is 0.74%. The metallic lithium is severely segregated in the alloy.

[0085] Comparative Example 5

[0086] Preparation of aluminum-lithium alloy by doping method: 400 kg of washed and dried aluminum ingots are placed in a crucible in a vacuum induction furnace, evacuated and filled with argon to maintain a slight positive pressure, heated to 750°C, and the aluminum is completely melted after 45 minutes. Take out 5.83 kg of metallic lithium obtained by electrolysis and vacuum-packed with aluminum foil to prepare 2195 aluminum-lithium alloy ingots. Use the bell jar method to put the metallic lithium wrapped in aluminum foil 300 mm below the aluminum liquid. After 5 minutes of melting, stir with argon for 25 minutes, cool to 710°C and cast into ingots by semi-continuous casting. The prepared aluminum-lithium alloy ingots are sampled and analyzed. The yield of metallic lithium is 72.39%, the highest lithium content is 1.98%, and the lowest is 0.84%. The metallic lithium is severely segregated in the alloy. Several black grooves with a depth of 2-4 mm, a width of 1-3 mm, and a length of 100-600 mm appear on the surface, such as Figure 6 As shown, the subsequent lathe cutting of the ingot is flammable.

[0087] Among them, Test Examples 1-7 in Table 2 are based on Example 1 to prepare LA141A magnesium-lithium alloy ingots, and steps S1-S4 are exactly the same as in Example 1; the parameters different from Example 1 in step S5 are the single furnace smelting amount (i.e., the weight of the magnesium ingot used) and the weight of the lithium-magnesium alloy element added, and the rest of the preparation process is the same. Similarly, Test Examples 8-14 in Table 3 are based on Example 2 to prepare 2195 aluminum-lithium alloy ingots, and steps S1-S4 are exactly the same as in Example 2; the parameters different from Example 1 in step S5 are the single furnace smelting amount (i.e., the weight of the aluminum ingot used) and the weight of the lithium-magnesium alloy element added, and the rest of the preparation process is the same. And the detection standards and methods of all embodiments, test examples and comparative examples in Tables 2 and 3 are the same.

[0088] From the results in Table 2 and Table 3, it can be seen that the traditional blending method can only prepare Mg-Li alloy ingots and Al-Li alloy ingots with small melting volumes (about 50kg). When preparing alloy ingots with large melting volumes, the surface quality of the alloy will not meet the standards, and there will be cracks or even black grooves. For details, please refer to Figure 4 and Figure 5 The schematic diagram of the 400kg grade LA141 magnesium-lithium alloy product is shown, and Figure 6 The appearance diagram of the 400kg grade 2195 aluminum-lithium alloy product is shown in the figure. Figure 4-Figure 6 This kind of product with substandard surface quality needs to be turned to remove cracks and black grooves before subsequent use, resulting in a lot of waste; at the same time, the alloy prepared by the doping method has a low lithium yield, resulting in a waste of lithium elements, and severe segregation, which will directly affect the strength, stiffness, modulus, etc. of the product. The Mg-Li alloy ingots and Al-Li alloy ingots prepared by the method of the present application, whether it is a small smelting amount of 50kg or a large smelting amount of 600kg, the appearance quality and elemental analysis of the prepared products meet the national standards for high-quality products, and can effectively meet the use scenarios of large alloy castings such as aerospace, and the lithium yield is significantly improved. The Mg-Li alloy ingots and Al-Li alloy ingots prepared by the technical method of the present application can be referred to Figure 2 The schematic diagram of the 400kg grade LA141 magnesium-lithium alloy product is shown, and Figure 3 The schematic diagram of the appearance of the 400kg grade 2195 aluminum-lithium alloy product is shown.

[0089] In summary, the present application provides a preparation process for high-quality Mg-Li and Al-Li alloys with large smelting quantities at normal pressure, which first uses a lithium source and Ca, Mg, and Al oxides to produce Li-Mg binary alloy elements through a reduction reaction, and then uses the Li-Mg binary alloy elements to smelt with magnesium ingots or aluminum ingots at normal pressure to obtain the corresponding Mg-Li or Al-Li alloys. The method of the present application can prepare large high-quality Mg-Li and Al-Li alloy castings at normal pressure, while improving the yield of lithium, without using electrolytic metallic lithium as a raw material for preparing magnesium-lithium or aluminum-lithium alloys, thereby avoiding the pollution of chlorine produced by traditional lithium electrolysis.

[0090] The above are all preferred embodiments of the present application, and the protection scope of the present application is not limited thereto. Therefore, any equivalent changes made according to the structure, shape, and principle of the present application should be included in the protection scope of the present application.

Claims

1. A process for preparing high-quality Mg-Li and Al-Li alloys with large smelting amount under normal pressure, characterized in that The following steps are involved: S1. Preparation of a composite oxide containing metallic lithium: The lithium source and the oxide are fully mixed and pressed into a cylinder, and calcined at a high temperature in a vacuum to obtain a composite oxide containing metallic lithium; S2. Preparation of Li-Mg binary alloy: The composite oxide prepared in step S1 is fully mixed with a reducing agent and a flux and then pressed into pellets, the pellets are subjected to a high-temperature vacuum thermal reduction reaction to generate a lithium and magnesium metal mixture gas, the metal mixture gas is cooled in a cooling collector to form a metastable metallic bond Li-Mg binary alloy condensed phase; S3. Paraffin purification: The Li-Mg binary alloy condensed phase collected in step S2 is placed in the melted paraffin together with the collector, so that the Li-Mg binary alloy condensed phase is completely melted and floats on the surface of the paraffin, and the high melting point impurities sink to the bottom of the paraffin, the temperature of the paraffin is lowered, and the Li-Mg binary alloy liquid phase floating on the surface of the paraffin solidifies into a solid phase and is removed; S4. Distillation, purification and ingot casting: The solidified Li-Mg binary alloy condensed phase removed from step S3 is distilled and purified in a distillation furnace protected by argon gas, and the purified Li-Mg binary alloy is smelted in a smelting furnace and a flux is added, and cast into a Li-Mg binary alloy ingot under argon gas protection, and is packed with aluminum foil and stored in an argon-filled container; S5. Magnesium and aluminum alloying: The washed and dried magnesium ingot or aluminum ingot is heated and melted in an electric furnace, and the Li-Mg binary alloy ingot obtained in step S4 is placed into the molten magnesium liquid or aluminum liquid for smelting, so that the Li-Mg binary alloy ingot is rapidly melted, stirred, cooled, and then cast to obtain the corresponding magnesium-lithium alloy ingot or aluminum-lithium alloy ingot; The mass ratio of the lithium source and the oxide in step S1 is (35-45):(65-55); the lithium source is one, two or three of anhydrous lithium carbonate, lithium nitrate and lithium hydroxide, and the oxide is a mixture of calcium oxide and magnesium oxide, or a mixture of aluminum oxide and magnesium oxide; the particle size D50 of the lithium source is 75-90 μm, and the particle size D50 of the oxide is 85-100 μm.

2. The process for preparing high-quality Mg-Li and Al-Li alloys with large smelting amount under normal pressure according to claim 1, characterized in that: The calcination under vacuum and high temperature in step S1 refers to calcination at a vacuum degree of 5-20 Pa and a temperature of 850-950° C. for 6-8 hours.

3. The process for preparing high-quality Mg-Li and Al-Li alloys with large smelting amount under normal pressure according to claim 1, characterized in that: The mass ratio of the composite oxide, reducing agent and flux in step S2 is (80-83):(15-17):(2-4), and the particle size D50 of the composite oxide, reducing agent and flux is 80-90 μm.

4. The process for preparing high-quality Mg-Li and Al-Li alloys with large smelting amount under normal pressure according to claim 3, characterized in that: The reducing agent in step S2 is any one of ferrosilicon, aluminum powder or carbon powder, and the flux is fluorite.

5. The process for preparing high-quality Mg-Li and Al-Li alloys with large smelting amount under normal pressure according to claim 1, characterized in that: The high-temperature vacuum thermal reduction reaction of the pellets in step S2 is carried out at a pressure of 5-10 Pa and 1100-1200° C. for 8-10 hours.

6. The process for preparing high-quality Mg-Li and Al-Li alloys with large smelting amount under normal pressure according to claim 1, characterized in that: The melting temperature of the Li-Mg binary alloy condensed phase in the paraffin in the cooling collector in step S3 is controlled to be 7-10° C. higher than the melting point of the Li-Mg binary alloy, and the melting time is 2-2.5 hours.

7. The process for preparing high-quality Mg-Li and Al-Li alloys with large smelting amount under normal pressure according to claim 1, characterized in that: In step S4, the Li-Mg binary alloy is purified by three-stage distillation in a distillation furnace. The distillation kettle in the distillation furnace is made of stainless steel. The three distillation temperatures are respectively controlled to be 15° C., 30° C., and 45° C. higher than the melting point of the Li-Mg binary alloy.

8. The process for preparing high-quality Mg-Li and Al-Li alloys with large smelting amount under normal pressure according to claim 1, characterized in that: When the Li-Mg binary alloy is melted in step S4, and when the magnesium ingot or aluminum ingot is heated and melted in step S5, a flux is added and protected by argon gas. The flux is a mixture of three compounds: LiCl, MgCl2 and LiF. The mass ratio of the three compounds is LiCl:MgCl2:LiF=(55-65):(4-21):(24-31).

9. The process for preparing high-quality Mg-Li and Al-Li alloys with large smelting amount under normal pressure according to claim 1, characterized in that: The metastable metallic bond Li-Mg binary alloy condensed phase is a compound Mg 2.49 Li and Mg 4.72 Li, in step S5, after the Li-Mg binary alloy reaches the melting point and melts, when it is close to 600°C, the compound Mg 2.49 Li and Mg 4.72 Li is decomposed into atomic Li and atomic Mg, and the atomic Li and atomic Mg are evenly distributed in the corresponding magnesium liquid or aluminum liquid through stirring.

Citation Information

Patent Citations

  • A continuous lithium refining device and method for lithium containing materials

    AU2020101985A4

  • Method for production of magnesium-lithium alloy by gaseous co-condensation method

    CN111097920A